Postural performance in the bipedal and unipedal stance of elite soccer players in different age categories - Mala, L.; Maly, T.; Zahalka, F. (Acta Kinesiologica, 2017)
Postural stability (PS) is considered to be a highly important factor for athletes. The aim of the study was to compare differences in PS performance in the bipedal and unipedal stance of soccer players in different age categories. Elite players in three age categories (Senior team (ST): n = 24, Junior team (U21): n = 20 and Youth team (U16): n = 20) participated in three tests of PS (wide stance with and without visual control and flamingo stance on the preferred and non-preferred leg). Analysis of variance (ANOVA) and Bonferroni`s post hoc tests were used for investigating the effect of visual control and leg preference on PS performance in elite soccer players. ANOVA revealed significant differences in total travelled way (TTW) among the observed groups (F(2,128) = 20.41, p < .01, çp 2 = .25) in bipedal stance tests. Visual control had a significant effect on the level of PS in the tested players (F(1,128) = 25.96, p < .01, çp 2 = .18). Additionally, in the performance of the flamingo test, ANOVA showed significant differences in TTW among the tested groups (F(2,128) = 6.25, p < .01, çp 2 = .09). Despite higher values in the non-preferred leg among all teams, limb preference had no significant effect on the level of PS in the tested players (F(1,128) = 1.64, p > .05, çp 2 = .01). The presented data can serve as a certain top standard for comparisons of PS performance in elite soccer players indifferent age categories, with the aim being to optimize and compensate for observed differences; this information can be useful in the development of strategies for injury prevention.